Dinámica Reciente de la Economía Risaraldense (2019)
This paper shows the results of a study of the economy in Risaralda between 1990 and 2005. It confirms that the problems are not just by the situation at the moment, since the participation of this department in the gross domestic product has been reduced and in 2006 was about 1,78%, that corresponds to 15th place in the GDP, between the 32 departments of the country. In terms of the GDP per capita, Risaralda was located in the 17 place in 2005, but in 1990 it was located in the 13 place, which indicated that it had a worse behavior during the period of time, mainly because the growth rate of the GDP is lower than the population´s growth rate. The revision of the complete period of time allows to warn that it is not a steady growth and that, on the contrary, during this past 15 years there have been some moments of financial slowdown and crisis. The most important sectors are the public administration, followed by construction and some services such as communications, transportation and broker services. Exports different than coffee have shown themselves dynamic in their growth; there is a decrease in participation of almost all of the industry groups, and some areas of production such as leather, shoes, rubber products, iron and steel are almost disappearing.